TEKNIK APLIKASI KONSORSIUM BAKTERI ENDOFITIK PENAMBAT N2 ASAL TUMBUHAN EKOSISTEM AIR HITAM KALIMANTAN TENGAH DALAM MENINGKATKAN PERTUMBUHAN DAN PENAMBATAN N2 TANAMAN PADI GOGO - Mieke R Setiawati; Tualar Slmarmata; Yuyun Sumarni; Dedeh H Arief; Dwi Andreas Santosa; Hari R Harlyadi (Research Center for Chemistry - LIPI, 2010)
This study was intended to derive an application technique of bacterial consortium obtained from plantation black water ecosystem of CentraKalimantan, and therefore to increase the nitrogen fixation and growth of the upland rice. The experiments were conducted in the Biology and Biotechnology Laboratory, Faculty of Agriculture, PadjadjaranUniversity, Jatinangor-West Java. The preliminary selection of inoculum source from the plantation ecosystem at black water ecosystem of Central Kalimantan produced 12 consortia of the endophytic bacterium that increase the growth of upland rice. Among of the 12 consortia, 2 consortia (did contribute nitrogen fixation consistently and so increase the growth of upland rice. The two consortia were a bacterial consortium (H) isolatedfrom the leaves of Waru plant (Dillenia pulchella) and a bacterial consortium (I) isolatedfrom Gemor plant (Alceodaphde sp.). Threefactorial of Complete-Random Design and triplo experiment was selected for the experimentaldesign of this study. First factor was consortium of endophytic nitrogen fixation bacterial with two stages (i1 = consortium H and i2 = consortium I). The second factor was the technique of endophytic nitrogen fixationbacteria application with two stages (aI = rice seed soaked in the bacterial suspension for 24 hours and a2= 1 MST old rice plant sprayed the bacterial suspension). The third factor was turbidity (population) of endophytic nitrogen fixation bacterial inoculum with 4 stages (Po=no inoculum control, PI=107 CFU.mtI, P2=109 CFU/mtI, P3= 1011CFU/ml). The CFU is a Colony-Forming Unit indicating microbes in aform of colony, initially, grew from single cell. The results of this experiment showed that the application technique of endophytic nitrogen fixation bacteria by soaking the upland rice seed in bacterial suspension containing 1011 CFU.mrI for 24 hours wasable to increase the growth and nitrogen fixation of the upland rice plant. Dry weight of the plant inoculated with consortia Hand I was respectively 0.084 and 0.097g while the nitrogenase activity of the upland rice plantinoculated with consortia Hand I was 254.0 and 225.0 nmol g